Konsep Tujuan Pendidikan Islam Perspektif Nilai-nilai Sosial-kultural - Rohman, Miftahur; Hairudin, Hairudin (Universitas Islam Negeri Raden Intan Lampung, 2018)
Islamic education as part of the national education system has a goal to beachieved. In the process, Islamic education can not be separated from theproblems faced. In today's postmodern era, Islamic education should be usedas a container for the seeds of tolerance to maintain harmony and peace. AlQuran and Hadith as the main source of Islamic education should bereinterpreted and integrated with other approaches. One approach that canbe integrated is to internalize the socio-cultural values in learning. Thisapproach offers a synthesis in order to face the seeds of intolerance that havebegun to grow in this nation's young generation. With the internalization ofthese values are expected to create a social harmony that can be madeprovision by the young generation of Muslims in public life.